ANALISIS IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI PADA PROYEK PEMBANGUNAN BUFFER AREA DI PELABUHAN SUNDA KELAPA - Sendy, Sendy; Manlian A. Simanjuntak, Ronald (Jurnal Teknik Sipil Giratory UPGRIS, 2025)
Accidents in construction projects are one of the factors that affect company performance and directly indicate that risk management in the project has not been properly implemented. If the Construction Safety Management System (CSMS) is thoroughly applied, the likelihood and risk of workplace accidents on construction projects can be identified early. This is done to reduce the number of accidents and construction failures, as any loss, no matter how small, is significant. The questionnaire is designed to generate quantitative data that can be objectively measured and statistically analyzed. The rating scale used in the questionnaire is taken from the appendix form for the implementation of CSMS in construction, allowing respondents to rate statements on an ordered scale and produce data that can be statistically interpreted without making comparisons with other variables. According to the CSMS Implementation Level Classification, the Buffer Area Development Project at Sunda Kelapa Port is categorized as "Satisfactory." This satisfactory implementation reflects the project's commitment to high standards of occupational safety and health, although there are still aspects that need to be improved to achieve a more optimal level of implementation. Overall, these results reinforce the conclusion that the project has been well-managed, and all parties involved have a strong understanding and commitment to implementing CSMS. This is a positive indication for the project's success and the safety of the workers involved